STRATEGI PENGEMBANGAN USAHA MIKRO MILIK MAHASISWA - Imron Rosyadi (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2013)
The purpose of this research is arrange a strategy model for developing micro and small enterprises owned by the student on the Colleges strategic role-based. Research conducted in the selected region: Surakarta, Sukoharjo, Klaten and Boyolali Regency. The data used is primary and secondary data. Primary data is obtained using the techniques of observation, focus group discussion (FGD) and in-depth interview on micro and small entrepreneur’s students in the area of research, the secondary data is obtained from various publication sources. Analytical method used is descriptive-analytic approach. This result showed that: (1) micro and small enterprises owned by student face various problems especially capital aspect, enterprises management and entrepreneurship skills; (2) the problems that have been identified is used a basis of arrangement a SWOT analysis from formulating a grand strategy and model development of micro and small enterprises (Figure 4.3); (3) The strategic role of the Colleges in developing micro and small enterprise: (a) formulating strategic for the developing of small and micro enterprises through: (i) the teaching of entrepreneurship and enterprises management soft skills-based and (ii) conducting education and training an intensive, systematic and integrated about enterprises management and entrepreneurship science and technology-based; (b) colleges synergize with Banks and HPMI for purposes related to the evaluation of the feasibility business plan, flanking business and business consultant for entrepreneurs students; (c) providing ease of access to capital for entrepreneurs students his business plan is considered feasible by a team of assessment.